Reflections on the effect of ideological elements present in the media that affect family relationships - Gómez Ibañez, Janett Melita (2022)
The media have become the most effective disruptive vehicle for the dissemination of ideological content that, over time, is inserted into family dynamics, generating an impact on social activity. For this reason, the question arose about what would be the elements of ideological content that are affecting family relationships and how are they transmitted? To answer this question, this research explores the existence of ideological content in the family system and how they are imperceptibly inserted through the media, disseminating their messages massively. In the search process, it was identified that biased information recreates alternate realities or false consciences, with messages loaded with beliefs and prejudices that are subtly implanted in families with poor communication and a conflictive climate, creating adverse effects on healthy coexistence. According to the statistical data found on family relationships, violence, discrimination, and exclusion in Peru, it is concluded that it is necessary to strengthen sustainable public mechanisms for information, guidance and adequate prevention on concepts that violate rights and responsibility for training to future.